Prevalence and factors associated with visual impairment in middle-aged and older Chinese population - Ye, Hanyuan; Zeng, Yun; Xiao, Hongxia; Yu, Jing; Liu, Yun; Zhang, Shuang; Zhang, Bingjie (Frontiers in Medicine, 2022)
Objective: To estimate the prevalence of vision impairment and to identify its associated factors in China. Methods: Data for this cross-sectional study were retrieved from the China Health and Retirement Longitudinal Study (CHARLS) for a total of 16,480 subjects who completed the questionnaire between June 2011 and March 2012. The prevalence of vision impairment was estimated considering the complex survey design and response rate. Associated factors were identified using weighted logistic regression analysis. Results: The overall prevalence of vision impairment among middle-aged and older Chinese adults was 6.22%. Regionally, Qinghai and Gansu provinces showed the highest vision impairment prevalence, while Shanghai showed the lowest vision impairment prevalence in China. Older age (OR = 1.888; 95% CI: 1.537–2.467) was correlated with a higher likelihood of vision impairment, while a non-alcohol intake (OR = 0.072; 95% CI: 0.018–0.246) was correlated with a lower likelihood of vision impairment. Hypertension (OR = 1.299; 95% CI: 1.189–1.467), diabetes (OR = 2.000; 95% CI: 1.163–3.765), lung diseases (OR = 1.795; 95% CI: 1.067–3.019), liver diseases (OR = 1.270; 95% CI: 1.221–2.876), stroke (OR = 1.135; 95% CI: 1.107–3.528), and heart disease (OR = 1.350; 95% CI: 1.104–1.708) were significantly associated with vision impairment. Conclusions: Geographic variations in the prevalence of vision impairment in China were defined, indicating such variations do exist in China. Age, alcohol intake, hypertension, diabetes, lung diseases, liver diseases, stroke, and heart disease were factors associated with vision impairment.